Remuneration of sales force: Variables that determine your success or failure - Torres Carballo, Federico (2016)
The remuneration to the sales force is a major issue in commercial organizations. What kind of incentives increase the selling effort to achieve the goals of the organization? With the combination of different incentive schemes it is possible to increase seller’s dedication? This is the first study applied in Costa Rica, using experimental techniques to address such issues. A set of sessions are conducted with more than 200 students, from careers related to business administration, to study sales contests with a compensation scheme, in which there is a first prize followed by several smaller prizes assigned to the achieved sales made by the seller. It was found that it is possible to reduce the effort to achieve organizational objectives when the subjects can communicate constantly.